Characterization of the tyrosine-hydroxylase immunoreactive components of the basal subpallium in sharks—toward an identification of a basal subpallial complex - Rodríguez-Moldes, Isabel; Sueiro, Catalina; Carrera, Iván; Quintana-Urzainqui, Idoia; Candal, Eva (Frontiers in Neuroanatomy, 2025)
Comparative studies on the forebrain across different model organisms are necessary to investigate the origin and degree of evolutionary conservation of this brain region and its derivatives. The catshark Scyliorhinus canicula has become a reliable model representative of cartilaginous fishes (Chondrichthyans), the oldest divergent lineage of extant gnathostomes (jawed vertebrates). Previous studies on the chemoarchitecture, connectivity, and development of the subpallium of S. canicula revealed the existence of subdivisions with an embryological origin and genetic specification similar to those of tetrapods, supporting homology with their basal ganglia and certain amygdaloid components. To better understand the evolutionary origin of these subpallial components, we present here a summary of the main neuroanatomical, chemoarchitectural, and developmental features of the area superficialis basalis of S. canicula, a nuclear aggrupation of the basal forebrain of all Chondrichthyans that has been related to the basal ganglia and the amygdala. Particular emphasis has been placed on characterizing the tyrosine hydroxylase-positive components of the subpallium to discern their involvement in the structural organization of putative basal ganglia homologs in the catshark. We propose a new interpretation that considers the area superficialis basalis as the central part of a subpallial complex formed also by its neighboring territories, where the basic components of the basal ganglia and the amygdala of gnathostomes would be integrated.